Bioaccumulation and translocation of polyhalogenated compounds in rice (Oryza sativa L.) planted in paddy soil collected from an electronic waste recycling site, South China. (October 2015) - Zhang, Yun; Luo, Xiao-Jun; Mo, Ling; Wu, Jiang-Ping; Mai, Bi-Xian; Peng, Yong-Hong
Highlights: The root accumulation factor was regulated by Log Kow of chemicals. Translocation of PHCs from root to aerial parts positively correlated with log Kow . Leaf accumulation exhibited a concentration-dependent mechanism. Abstract: The bioaccumulation and translocation of polyhalogenated compounds (PHCs) in rice planted in the paddy soils of an electronic waste (e-waste) recycling site were investigated, along with the effect of contaminated soils on rice growth. The PHCs included polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), decabromodiphenyl ethane (DBDPE), 1, 2-bis(2, 4, 6-tribromophenoxy) ethane (BTBPE), and dechlorane plus (DPs). The morphological development and all measured physiological parameters of rice plants except for peroxidase were significantly inhibited by e-waste contaminated soils. Specifically, soil-root bioaccumulation factors (RCFs) increased with increasing logarithm of octanol–water partition coefficient (log Kow ) for PCBs, but decreased for PBDEs. During translocation from root to stem, translocation factors (TFs) and log Kow were positively correlated. However, the accumulation mechanism in the leaf was concentration-dependent. In the high concentration exposure group, translocation play more important role in determination PHCs burden in leaf than atmospheric uptake, with log TF (from stem to leaf) being positively correlated with log Kow . In contrast, in the low exposure and control groups, log TF (from stem to leaf) was negatively correlated with log Kow . In addition, Syn -DP was selectively accumulated in plant tissues. In conclusion, this study demonstrates that e-waste contaminated soils affect rice growth, revealed the rule of the bioaccumulation and translocation of PHCs in rice plants.